Life skills programmes for chronic mental illnesses - Patraporn Tungpunkom (2018)
Background: Most people with schizophrenia have a cyclical pattern of illness characterised by remission and relapses. The illness can reduce the ability of self-care and functioning and can lead to the illness becoming chronic and disabling. Rehabilitation is one of the important parts of treatments. Life skills programmes, emphasising the needs associated with independent functioning, are often a part of the rehabilitation process. These programmes, therefore, have been developed to enhance independent living and the quality of life for people with schizophrenia living in the community. Objectives: To review the effectiveness of life skills programmes with standard care or other comparable therapies for people with chronic mental health problems. Search strategy: We searched the Cochrane Schizophrenia Group Trials Register (May 2007) which is based on regular searches of BIOSIS, CENTRAL, CINAHL, EMBASE, MEDLINE and PsycINFO. Hand searches and scrutiny of references supplemented this process. We inspected references of all identified studies for further trials. Selection criteria: We included all relevant randomised or quasi-randomised controlled trials for life skills programmes versus other comparable therapies or standard care involving people with serious mental illnesses. Data collection and analysis: We extracted data independently. For dichotomous data we calculated relative risks (RR) and their 95% confidence intervals (CI) on an intention-to-treat basis, based on a random effects model. We calculated numbers needed to treat/harm (NNT/NNH) where appropriate. For continuous data, we calculated weighted mean differences (WMD) again based on a random effects model. Main results: We included four randomised controlled trials with a total of 318 participants. These evaluated life skills programmes versus standard care, or support group.We found no significant difference in life skills performance between people given life skills training and standard care (Patterson 2003, n=32,WMD -1.10 CI -7.8 to 5.6). Life skills training did not improve or worsen study retention (n=60, 2 RCTs, RR 1.16 CI 0.4 to 3.4). We found no significant difference in PANSS positive, negative or total scores between life skills intervention and standard care. Depression scores (HAM-D) did not reveal any significant difference between groups (Patterson 2003, n=32,WMD -0.70 CI -4.1 to 2.7). We found quality of life scores to be equivocal between participants given life skills training (Patterson 2003, n=32, WMD -0.02 CI -0.1 to 0.03) and standard care. Life skills compared with support groups also did not reveal any significant differences in PANSS scores, quality of life, or social performance skills (Patterson 2006, n=158, WMD -0.90 CI -3.4 to 1.6). Authors' conclusions: Currently there is no good evidence to suggest life skills programmes are effective for people with chronic mental illnesses.More robust data are needed from studies that are adequately powered to determine whether life skills training is beneficial for people with chronic mental health problems. Copyright © 2009 The Cochrane Collaboration. Published by John Wiley & Sons, Ltd.